Batak Customary Marriage: A Study of the Prohibition of Same-Clan Marriage and Its Relevance in the Contemporary Era - Solin, Siti Dian Natasya; Djawas, Mursyid; Amri, Aulil; Sugirman, Andi; Zubair, Asni (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study discusses Batak customary marriage focusing on the prohibition of same-clan marriage and the practice of same-clan marriage in Batak custom. The main problem studied is the prohibition of intermarriage in Batak society from a fiqh perspective in relation to modern times. This study used a qualitative approach, i.e., a humanistic approach that places humans in research as the main subject in social events. The study was a type of field research, which involves direct observation and examination of facts in the research site, taking the data as primary sources. The findings of this study reveal that the concept of marriage in Batak custom is exogamy, which prohibits marriages between people of the same clan. In Batak custom, people of the same clan are blood relatives or descendants from the father’s line. Batak people who violate this customary law will be subject to customary sanctions. In the current context, the decline in customary values has been influenced by urbanization and higher education, which prioritize modern thinking over traditional one. Education provides certain values for humans, e.g., opening people’s minds, accepting new ideas, and thinking scientifically. Education teaches humans to be able to think objectively, which will give them the ability to assess whether or not their community’s culture can meet the needs of the times. Further, from the perspective of fiqh munakahat, not all family ties are forbidden to marry. Only those related to the provisions of muabbad (permanent prohibition) and ghairul muaabad (temporary prohibition) are prohibited. People from the same clan who have no kinship relationship are still lawful to marry.